2009
DOI: 10.1121/1.3082114
|View full text |Cite
|
Sign up to set email alerts
|

A realization of sound focused personal audio system using acoustic contrast control

Abstract: A personal audio system that does not use earphone or any wire would have great interest and potential impact on the audio industries. In this study, a line array speaker system is used to localize sound in the listening zone. The contrast control [Choi, J.-W. and Kim, Y.-H. (2002). J. Acoust. Soc. Am. 111, 1695-1700] is applied, which is a method to make acoustically bright zone around the user and acoustically dark zone in other regions by maximizing the ratio of acoustic potential energy density between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 5 publications
0
63
0
Order By: Relevance
“…The latter technique is noted here to be a cancellation method, distinct from beamforming, as it creates cancellation regions in addition to focusing the sound energy. ACC has been the foundation of much subsequent sound zone attention and has been applied to personal computers (Chang et al, 2009a;Chang et al, 2009b), aircraft seats (Elliot and Jones, 2006;Jones and Elliott, 2008), and hand held devices (Elliott et al, 2010). An alternative cancellation method known as acoustic energy difference maximization (AEDM) was proposed by Shin et al (2010) with a modified cost function negating the need for matrix inversion and allowing for adjustment of the array control effort via a parameter in the cost function.…”
Section: Introductionmentioning
confidence: 99%
“…The latter technique is noted here to be a cancellation method, distinct from beamforming, as it creates cancellation regions in addition to focusing the sound energy. ACC has been the foundation of much subsequent sound zone attention and has been applied to personal computers (Chang et al, 2009a;Chang et al, 2009b), aircraft seats (Elliot and Jones, 2006;Jones and Elliott, 2008), and hand held devices (Elliott et al, 2010). An alternative cancellation method known as acoustic energy difference maximization (AEDM) was proposed by Shin et al (2010) with a modified cost function negating the need for matrix inversion and allowing for adjustment of the array control effort via a parameter in the cost function.…”
Section: Introductionmentioning
confidence: 99%
“…1 Generally, two different kinds of zones are created by the personal audio systems-the bright zone, a region where a desired sound pressure level is reproduced, and the dark zone, where the sound pressure level needs to be attenuated. For this purpose, Choi and Kim 2,3 used the acoustic contrast as a measure of performance and proposed the acoustic contrast control (ACC) approach to maximize this contrast.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, only a few studies that validate sound field control with loudspeakers experimentally have been published. [10][11][12][13][14][15] These studies have shown that the sound field control is feasible as expected from the simulations, but the exterior region of the loudspeakers array has not been considered.…”
mentioning
confidence: 90%